2020
DOI: 10.15766/mep_2374-8265.11021
|View full text |Cite
|
Sign up to set email alerts
|

A Paging Training Program for a Fourth-Year Internship Readiness Course

Abstract: Introduction New medical interns face a steep learning curve as they must manage complex medical scenarios, many of which they have only seen before in a classroom setting. To ameliorate these challenges, medical schools are increasingly including courses designed to address the transition from student to doctor. One of the biggest challenges for new interns is learning to triage and manage nursing pages, so we designed a mock paging program incorporated within our fourth-year transitions course. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…There was one qualitative study [ 4 ]. Among others, seven articles used a mixed methods design, including a quantitative design as a major approach with qualitative data collection such as a focus group interview [ 14 , 29 ], survey comments [ 7 , 30 32 ], and audiovisual recorded comments [ 33 ]. Reviewers evaluated the quality of these mixed methods articles using a JBI checklist for quantitative designs if the primary technique was quantitative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There was one qualitative study [ 4 ]. Among others, seven articles used a mixed methods design, including a quantitative design as a major approach with qualitative data collection such as a focus group interview [ 14 , 29 ], survey comments [ 7 , 30 32 ], and audiovisual recorded comments [ 33 ]. Reviewers evaluated the quality of these mixed methods articles using a JBI checklist for quantitative designs if the primary technique was quantitative.…”
Section: Resultsmentioning
confidence: 99%
“…The number of learners varied by type of simulation and the duration of the curriculum, from 11 [ 29 ] in an avatar-based virtual continuing medical education (CME) workshop to 305 [ 5 ] in a statewide mandatory course offered year-round. The most common areas of professional expertise among learners were medical [ 6 , 7 , 10 , 14 , 17 19 , 29 , 33 42 ], nursing [ 11 , 31 , 43 ], multi-professional [ 4 , 5 , 13 , 44 ], interprofessional [ 30 , 32 ], and dental [ 45 ]. One study [ 46 ] reported on an educational intervention for research coordinators.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These courses often focus on discrete clinical skills such as answering pages, postacute care, handoff, end-of-life care, and so on. 2 7 As these courses have grown nationally, a TTR Compendium began in 2023 to house TTR resources used in different courses. 8 As with the other TTR content currently published, the compendium focuses on clinical skills like cross-cover, informed consent, and delivering serious news.…”
Section: Introductionmentioning
confidence: 99%